Urodynamic Studies in Cases of Urinary Incontinence and Pelvic Organ Prolapse: Key Messages - Chughtai, Novera G.; Kashif, Urooj (Medical Research and Its Applications Vol. 6, 2024)
There is conflicting evidence regarding the indications of urodynamic studies (UDS) and various guidelines. American Urogynecologic Society (AUGS), National Institute of Health and Care Excellence (NICE), and WHO provide variant indications for UDS testing. For developing countries, there is no data to support the usefulness of UDS. The purpose of this chapter is to derive important conclusive messages as a guideline for future practices. For example, in cases of SUI and OAB, UDS are not required, but patients with complex MUI, chronic LUTS, and neurogenic bladder warrant UDS. UDS can be done in cases of LUTS for a better understanding of LUTS in terms of available symptoms, other hidden symptoms, correlation between symptoms and prediction of impact on the upper urinary tract and other clinical consequences and prediction of treatment outcome, side-effects of therapeutic options, or assessment of causes leading to failure of previous intervention.